(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
pain played only a minor role during the first few years of China’s almost unconditional opening up to the West, though it had established diplomatic relations with the People’s Republic of China in 1973. After the Tiananmen Square incident and the sanctions imposed by the West in 1989, including the arms embargo that is still in place, the support that Madrid showed for the continuity of the economic reforms and the opening-up policy launched by Deng Xiaoping in 1978 significantly changed China’s perception of Spain. Beijing very much appreciated Spain’s understanding. From then on, it was considered "China’s best friend in Europe" and fifteen years later Beijing upgraded bilateral relations to the level of a Comprehensive Strategic Partnership. The objective of this article is to analyse the reasons for this cooperation and the aspirations of both countries